Progressive symmetric erythrokeratoderma with nephrotic syndrome: Coincidence or new association? - S Sacchidanand; M S Sahana; Sushruth G Kamoji; G S Asha (Wolters Kluwer Medknow Publications, 2013)
Progressive symmetric erythrokeratoderma (PSEK) is a rare genodermatosis with variable inheritance. It is characterized by symmetrical, erythematous, and hyperkeratotic plaques on the extremities. We report a case of a 15-year-old boy with PSEK of autosomal recessive inheritance associated with nephrotic syndrome.